Evaluating the Components of Marketing Mix (7Ps) of Iran's Volleyball Super League - Siavash Khodaparast Sareshkeh; Seyed Mohammad Hossein Razavi; Morteza Rezaee Soufi; Ali Mohammad Safania (The Society of Aging and Physical Activity (SAPA), 2016)
The aim of this study is to evaluate the sport marketing mix and its seven elements (product, price, promotion, place, public relations, people, and physical evidence) in Iran’s volleyball super league from the viewpoint of ministry of sport and volleyball federation managers in two conditions, namely existing and optimal. For this purpose, 102 subjects, among them the official staffs in the ministry of youth and sport up to general managers and volleyball federation’s officials up to the managers of the sub-divisions, filled in the researchers’ constructed questionnaire with an appropriate validity and internal reliability of 91% (Cronbach alfa). Based on the findings taken from the viewpoints of the staffs in the ministry of youth and sport up to general managers, and volleyball federation’s officials up to the managers of the divisions, CEOs, leaders, coaches and academics, it has been found that in the existing condition, the component of product enjoyed the highest mean. Other components including price, physical evidence, public relations, promotion, and distribution had lower means (in order mentioned). In the optimal condition, the public relations variable had the highest mean, and other components had lower means. However, there was a statistically significant difference between the two existing and mix optimal conditions and their 7 components such that according to the rank means, the existing condition had a lower score compared to the optimal one. This means that in the existing condition, less attention has been paid to the mix elements.